Corruption and economic growth of Peru, 2010-2019 - Olivera Cáceres, Jesús Amadeo (2020)
The objective of this research was to analyze the relationship between corruption and economic growth in Peru during the period 2010-2019. The methodology had a quantitative approach, basic type, non-experimental design, of relational level, sought to analyze the relationship between corruption and economic growth in Peru, 2010-2019. It was cross- sectional because it collected data over a given period; for this purpose, documentary analysis was applied, gathering information in order to relate and measure the study variables, carry out the corresponding regressions and comparisons. Finally, it was established that there is a relationship between corruption and Peru's economic growth in the 2010-2019 period. The results determined that economic growth in Peru has decreased in terms of GDP (8.5 to 4.2 %). It was found that Peru's corruption score for the period 2010-2019 averaged 2.2 to 2.8, ranking 35th in 2010, and 36th in 2019 (according to Transparency International's world ranking), showing a constant in Peru's corruption index.